Existence of time-periodic solutions to incompressible Navier-Stokes equations in the whole space - Xianpeng Hu (Electronic Journal of Differential Equations, 2005)
In this article, we assume that the force field acting over a fluid is periodic on time and the velocity of the liquid is zero at spatial infinity. We prove the existence of time-periodic solutions to the system governing the motion of an incompressible fluid filling the whole space.